Restricted TcR [beta] chain CDR3 clonotype is associated with resolved acute hepatitis B subjects - Xiao, Dangsheng; Wang, Ju; Chen, Zhitao; Jin, Xiuyuan; Xie, Yirui; Yan, Dong; Yang, Jiezuan (BMC infectious diseases, 2021)
T cells play an important role in the prognosis of hepatitis B virus (HBV) infection, and are involved in the seroconversion of a patient from HBsAb negative to positive. To compare the T-cell receptor [beta]-chain variable region (TcRBV) complementarity-determining region 3 (CDR3) in subjects with or without hepatitis B surface antigen (HBsAg) convert to hepatitis B surface antibody (HBsAb), the TcRBV was determined using high throughput sequencing (HTS). The clonotype and diversity of CDR3 in peripheral blood mononuclear cells of subjects with resolved acute hepatitis B (AHB, HBsAb+, HBsAg-) (n = 5), chronic hepatitis B (CHB, HBsAb-, HBsAg+) (n = 5), and healthy controls (HC, HBsAb-, HBsAg-) (n = 3) were determined and analyzed using HTS (MiSeq). The overlapping rate of CDR3 clones of any two samples in AHB group was 2.00% (1.74% ~ 2.30%), CHB group was 1.77% (1.43% ~ 2.61%), and HC group was 1.82% (1.62% ~ 2.12%), and there was no significant difference among the three groups by Kruskal-Wallis H test. However, among the top 10 cumulative frequencies of clonotypes, only the frequency of clonotype (TcRBV20-1/BD1/BJ1-2) in AHB group was lower than that of HC group (P < 0.001). Moreover, exclude the 10 top clonotypes, there are 57 markedly different frequency of clones between AHB and CHB groups (18 clones up, 39 clones down), 179 (180-1) different clones between AHB and HC groups, and 134 different clones between CHB and HC groups. With regard to BV and BJ genotypes, there was no significant different frequency among the groups. Furthermore, there was no significant difference in the diversity of TcRBV CDR3 among the three groups (P > 0.05). Thus, there are 57 TcRBV clonotypes that may be related to HBsAg seroconversion of AHB subjects, but the diversity of TcRBV CDR3 is not significantly related to the HBsAb positive status.